(untitled) (Altre Modernità, 2019)
This article, based on a methodology coming from the Law/Literature studies, aims to establish the intertextuality between the case Gelman v. Uruguay (ruled by the Inter-American Court of Human Rights) and the literary and para-literary works of Argentinian writer Juan Gelman. The comparison between these two different archives allows to glimpse the events surrounding the disappearance of several people from Gelman’s family within Operación Cóndor, a military occurred during the dictatorships in the Southern Cone. In fact, such painful events are better understood and resolved in court if we take into account the power of the words of Gelman’s writings, which help fill in the gaps of the sentence. Our hypothesis is that in order to understand issues such as the rule of evidence or legal redress in the human rights context, literary texts can occupy, contrary to what has been sustained by legal doctrine, a transcendent place in a trial. This, at the same time, tries to demonstrate the power of literature to enter into certain legal documents, as well as the need to question de excluding divisions between Law and Literature.